Ultrasensitive bioassaying of HER-2 protein for diagnosis of breast cancer using reduced graphene oxide/chitosan as nanobiocompatible platform - Nasrollahpour, Hassan; Isildak, Ibrahim; Rashidi, Mohammad-Reza; Hashemi, Esmat Alsadat; Naseri, Abdolhosein; Khalilzadeh, Balal (SPRINGER WIEN, 2021)
Background: In this label-free bioassay, an electrochemiluminescence (ECL) immunosensor was developed for the quantification of breast cancer using HER-2 protein as a metastatic biomarker. Method: For this purpose, the ECL emitter, [Ru(bpy)(3)](2+), was embedded into biocompatible chitosan (CS) polymer. The prepared bio-composite offered high ECL reading due to the depletion of human epidermal growth factor receptor 2 (HER-2) protein. Reduced graphene oxide (rGO) was used as substrate to increase signal stability and achieve greater sensitivity. For this, rGO was initially placed electrochemically on the glassy carbon electrode (GCE) surface by cyclic voltammetry (CV) technique. Next, the prepared CS/[Ru(bpy)(3)](2+) biopolymer solution was coated on a drop of the modified electrode such that the amine groups of CS and the carboxylic groups of rGO could covalently interact. Using EDC/NHS chemistry, monoclonal antibodies (Abs) of HER-2 were linked to CS/[Ru(bpy)(3)](2+)/rGO/GCE via amide bonds between the carboxylic groups of Ab molecules and amine groups of CS. The electrochemical behavior of the electrode was studied using different electrochemical techniques such as electrochemical impedance spectroscopy (EIS), differential pulse voltammetry (DPV) and square wave voltammetry (SWV) and also ECL tests. Results: After passing all optimization steps, the lower limit of detection (LLOQ) and linear dynamic range (LDR) of HER-2 protein were practically obtained as 1 fM and 1 fM to 1 nM, individually. Importantly, the within and between laboratory precisions were performed and the suitable relative standard deviations (RSDs) were recorded as 3.1 and 3.5%, respectively. Conclusions: As a proof of concept, the designed immunosensor was desirably applied for the quantification of HER-2 protein in breast cancer suffering patients. As a result, the designed ECL-based immunosensor has the capability of being used as a conventional test method in biomedical laboratories for early detection of HER-2 protein in biological fluids.
Keywords: HER-2; ECL; Bioassay; Breast cancer; Biomedical analysis; Ruthenium; Protein; Biocompatible polymer; Chitosan; Biotechnology; [Ru(bpy)(3)](2+); Oncology; Science & Technology - Other Topics